Spatial distribution of eggs, larvae and juveniles of eyebrow goby (Oxyurichthys opthalmonema) in Batan Bay estuary, Aklan - David, Alemar V. (2019.)
To understand better the biology of eyebrow goby Oxyurichthys ophthalmonema, the spatial distributions of its eggs larvae and juveniles were investigated in Batan Bay Estuary, Aklan from October 2016 to September 2017 by employing a fisheries-independent methodology. Nesting grounds were located through burrow assessment followed by physic-chemical characterization of identified nesting grounds. Fifteen stations were established all over the study area. Results showed that O. ophthalmonema burrows were present in mudflats all over the study area. Of the 196 burrows assessed in detail, only 34 (17%) burrows had the presence of nesting adult O. ophthalmonema. For the spatial distribution of eggs, they were only found in Moto, Jalas and kapispisan burrows. The highest observed density was obtained in Kapispisan at 5 eggs/burrow. For the spatial distribution of larvae, they were only found in 9 stations with the Jalas showing the highest density at 32 larvae per 100m3. For the spatial distribution of juveniles, they occurred in all stations but the density was higher in Kapispisan at 4 juveniles per 1000m2. The nesting grounds are located near the upper river tributaries with substantial mudflats and mangrove forest cover. The physic-chemical characteristics of the nesting grounds were as follows : 24.50-26.67 ppt for salinity, 29.75-31.250C for water temperature, 3.26-3.55 for sediment pH (dry weight sediment, DW), 29.82-77.89 ug/g for iron (DW sed), and 0.52-1.15% organic matter (DW sed). The physic-chemical characteristics of the water and sediments of Batan Bay Estuary is favorable to nesting of O. ophthalmonema. There is need, therefore, to protect these habitats from threats that may negatively affect the nesting of O. ophthalmonema.
Thesis- M.S. Fisheries - Institute of Marine Fisheries and Oceanology, College of Fisheries and Ocean Sciences, University of the Philippines Visayas.
Keywords: Spatial distribution; Eyebrow goby; Oxyurichthys opthalmonema; Batan Bay Estuary, Aklan